Automatic Pet Feeder Rotational Model Using MQTT and Mobile Application - Mahadiputra, Putu Gede Krisna; Suarjaya, I Made Agus Dwi; Wibawa, Kadek Suar (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Udayana, 2024)
Automatic pet feeding systems with dispenser models have limitations on the type of feed that is only accomodate dry food, while pets (cats) with a tendency consuming dry food are prone to disease in the urinary system. This research focuses on designing a rotational model automatic pet feeding system that can accommodate both dry food and wet food, also set the feeding time through mobile applications via MQTT by utilizing an ESP32 microcontroller connected to a 5V stepper motor, RTC and load cell sensor. The system has success rate about 90% on pet feeding automation, but the container upper fold has difference angel about 5.4o with the expected position (error rate 6%). Every weight sensor has the successive error rates are 1.41% (1st feed block), 1.91% (2nd feed block), and 0.68% (3rd feed block). The Android application takes only 1-1.5 seconds to displaye the latest feed weight data.